Clinical research should be a priority in the NHS – but what do genito-urinary medicine clinic staff think?. (February 2015) - Roberts, Rosa; Perry, Nicky; Phillips, Alan; Richardson, Daniel; Soni, Suneeta
Clinical research improves patient care and is a government priority. We sought the opinions of genito-urinary medicine clinic staff regarding undertaking research, any barriers they perceived, and methods to optimise study recruitment. Questionnaires were offered to everyone working in the genito-urinary medicine clinic over a one-week period. In addition, four focus groups were held with genito-urinary medicine clinic staff. Forty-three questionnaires were completed. All respondents stated that research was important; however, 14.0% worried that it affected patient care and 16.3% would rather see patients without having to consider research. Doctors were more likely to enjoy discussing studies than other healthcare staff ( p  = 0.029) and were less likely to think that too many studies were being conducted at one time ( p  = 0.027). Forty staff attended the focus groups. Time, knowledge of studies, difficulty in broaching the topic of research and patient factors were cited as barriers to recruitment. Suggestions to improve recruitment included: greater multi-disciplinary team involvement; improving staff research knowledge; streamlining the research process; and patient education. Reasons for different attitudes between staff disciplines towards research included different training pathways and incentives to conduct research. The recommendations staff have made to help drive recruitment should be implemented in the genito-urinary medicine clinic.